Preparation of chitin fastening Ag@AgCl composite film with decontamination properties by one step coagulation method. (1st March 2019) - Yi, Chunwang; Liu, Jingkai; Meng, Deqian; Lv, Jing; Zhang, Xiaomin; shu, You; Su, Shengpei; Zhu, Jin
Abstract: A chitin-fastening Ag@AgCl composite film with decontamination properties was successfully prepared by one-step coagulation method of the chitin- LiCl/Dimethyl Acetamide (DMAc) solution with AgNO3 . In this process, AgCl was formed in a chitin solution with the addition of AgNO3 solution, and with the help of excess Cl − a solution of AgCl was formed. AgCl nanocrystals embedded on the surface of chitin were obtained after the solution was put into coagulation bath. The AgCl nano-crystals embedded on the surface of chitin film could be partly transformed into the Ag@AgCl by appropriate visible-light irradiation in the air. In order to explore the morphology and the formation mechanism of the composites, the well-prepared films were characterized by scanning electron microscopy (SEM), X-ray powder diffraction (XRD), Fourier transformation infrared spectroscopy (FTIR), X-ray photo-electron spectroscopy (XPS), thermogravimetric analysis (TGA), ultraviolet spectro-photometry and UV–visible absorption spectrum. The decontamination ability and recyclability of composite film was evaluated by the degradation rate of methyl orange (MO) in recycling process. By comparison, the Ag@AgCl fastened in chitin matrix was more stable than fastened by cellulose matrix. Its photo-degradation efficiency could be still retained up to 95% after 5-cycle testing. Meanwhile, the composite film could be also kept excellent mechanical properties. This work provided a simple pathway to construct the functional chitin film which could be applied as a kind of stable recycling decontamination materials.